Translating Calvino: challenges and opportunities. Five proposals for Calvino’s translators in the new millennium. - Bosca-Malin, Oana (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Translating Calvino: challenges and opportunities. Five proposals for Calvino’s translators in the new millennium. This Paper suggests an application of Calvino’s concepts described in Six memos For the Next Millenium at the translation of three of his novels – Le città invisibili, Il sentiero dei nidi di ragno e Ultimo viene il corvo. Each of Calvino’s concepts (lightness, quickness, exactitude, visibility, multiplicity and consistancy) is being defined according to the Italian writer, then identified in his practical manifestations in the three novels and afterwards adapted at the translation process. The result is a possible mechanism of translation and a set of suggestions for Calvino’s translators.